2010
DOI: 10.4049/jimmunol.1000115
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 Signaling Stimulates the Innate Production of IL-17 and IL-22 by CD3negCD127+ Immune Cells in Spleen and Mucosa

Abstract: Material Supplementary 5.DC1http://www.jimmunol.org/content/suppl/2010/06/21/jimmunol.100011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
125
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 52 publications
17
125
0
Order By: Relevance
“…Recent studies have shown that LTi cells constitutively express IL-23 and rapidly upregulate IL-17 secretion after in vivo challenge with zymosan (16), suggesting that they play a role in innate immune responses. In line with this study, two groups reported that LTi-like cells produce IL-17 and IL-22 in stimulation with flagellin, a TLR5 ligand (17), and Pam3CSK, a TLR2 ligand, in an indirect manner (18).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Recent studies have shown that LTi cells constitutively express IL-23 and rapidly upregulate IL-17 secretion after in vivo challenge with zymosan (16), suggesting that they play a role in innate immune responses. In line with this study, two groups reported that LTi-like cells produce IL-17 and IL-22 in stimulation with flagellin, a TLR5 ligand (17), and Pam3CSK, a TLR2 ligand, in an indirect manner (18).…”
Section: Introductionsupporting
confidence: 59%
“…Although the function of TLRs in antigen-presenting cells has been extensively studied, the expression and function of TLRs in splenic LTi cells are not well known. Recently, it was reported that human LTi-like cells express IL-5, IL-13, and IL-22 after activation with TLR2 ligands (18), and mouse LTi-like cells in the spleen and mucosa produce IL-17 and IL-22 upon stimulation with TLR5 ligand (17).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens, such as Citrobacter rodentium, Mycoplasma pneumoniae and Candida albicans, and PAMPs from pathogens, such as the TLR5 agonist flagellin, can induce IL-17C expression in the intestine, 25,159 lung, 160 kidney, 161 and tongue. 162 On a cellular level, several pathogens (that is, Pseudomonas aeruginosa, Haemophilus influenza, Staphylococcus aureus, Citrobacter rodentium and Candida albicans) trigger IL-17C production from bronchial epithelial cells, 163 keratinocytes, 164 intestinal epithelial cells, 25 and kidney epithelial cells.…”
Section: Il-17cmentioning
confidence: 99%
“…IL-17 is now best known as the signature cytokine secreted from the recently characterized T h 17 cells, however numerous innate cells can also produce IL-17, including innate-like γδ intraepithelial lymphocytes (IEL), natural killer (NK) T cells, lymphoid tissue inducer (LTi)-like cells, Paneth cells, and neutrophils, as well as other unidentified cell types (Buonocore et al, 2010;Cua & Tato, 2010;Doisne et al, 2011;L. Li et al, 2010;Maele et al, 2010;Michel et al, 2007;Shibata et al, 2007;Takahashi et al, 2006;Takatori et al, 2008). In the context of the intestinal mucosa, γδ IELs are currently the best-characterized innate sources of IL-17.…”
Section: Interleukin-17mentioning
confidence: 99%